Efficiency of the organization of the government service and its implementation in the public governance system - Yaremko, I. (Видавництво Львівської політехніки, 2020)
The issues of efficiency and rational organization of the civil service as an object of research of domestic and foreign scientists and practitioners, international non-governmental organizations are considered. Key factors of influence of the global and national social environment are analyzed with the emphasis on their influence on the level of effective functioning and construction of the civil service system. The criteria of openness, transparency, professionalism, efficiency and modernization for establishing ways of adaptation of national state institutions to European standards and improving the level of efficiency of public administration are evaluated. The main problems are revealed in the article and some aspects of forming of adaptive state administration which efficiency of functioning will provide growth of capacity and consolidation of strategic positions of economy of Ukraine will be offered, will increase opportunities for social requests of the population. On the basis of the defined systematic methodology for this research and selected methods and tools, some aspects of forming a system of criteria that can objectively evaluate and improve the effectiveness of the functioning of the public service in the public administration system are proposed.
Keywords: government; public service; efficiency; criteria system; assessment approaches and methods; international performance indices; D81; E61; F; 21; G28; 353; 340.134; 338.64